METAL OXIDE AND CARBON COMPOSITE-BASED ANODE MATERIALS FOR LOW-TEMPERATURE LITHIUM-ION BATTERIES - Issatayev, Nurbolat (Nazarbayev University School of Engineering and Digital Sciences, 2025)
Renewable energy is essential for creating a sustainable future, but its full potential can only be achieved with the advancement of efficient and eco-friendly energy storage systems. Lithium-ion batteries are the most efficient among contemporary technologies. Nonetheless, their sustainability and diminished efficiency at sub-zero temperatures present considerable challenges. In particular, conventional graphite anodes exhibit sluggish reaction kinetics at low temperatures, retaining approximately 12% of their room-temperature capacity at −20 °C. Moreover, restricted lithium-ion diffusion typically leads to lithium plating and dendrite development, thereby increasing the risk of short circuits and device malfunction. These issues underscore the urgent need for new anode materials that combine sustainability with superior electrochemical performance at low-temperature settings. Therefore, this thesis concentrates on the design and development of innovative anode materials, highlighting environmentally friendly synthesis methods and the combination of high specific capacity with improved low-temperature electrochemical performance. Unlike approaches that depend on specialized electrolyte formulations, this work demonstrates that carefully engineered anode materials alone can substantially enhance low-temperature lithium-ion battery performance using standard electrolytes. Through the introduction of porosity, heteroatom doping, and artificial interphase layers, the designed anodes significantly improve lithium-ion transport and effectively suppress dendrite formation under subzero conditions. During the research, three innovative anode materials were synthesized using sustainable, cost-effective, and scalable processes. The first strategy produced porous nitrogen-doped hard carbon from date seed biowaste, modified with lithium fluoride to form a stable artificial solid electrolyte interphase. This design delivered an outstanding 280 mAh/g at −20 °C at 0.1 C after 100 cycles and 72 mAh/g at 2 C after 500 cycles, with excellent high-rate capability at room temperature. The second approach integrated green-synthesized tin dioxide nanopowder into a conductive hard carbon matrix, achieving an impressive 660 mAh/g at −20 °C after 100 cycles and maintaining 383 mAh/g even at −30 °C, thanks to synergistic conductivity and mechanical buffering. The third design, germanium dioxide/hard carbon coated with a flexible polymeric layer, showed remarkable stability, maintaining 370 mAh/g at −20 °C after 80 cycles, while also delivering nearly 800 mAh/g at 500 mA/g at room temperature. Collectively, these designs form a coherent materials engineering framework that merges sustainable synthesis, synergistic component interactions, and targeted surface engineering to address the fundamental causes of low-temperature degradation in lithium-ion batteries. By advancing anode material design beyond electrolyte optimization, this work provides a pathway to high-capacity, cold-climate-compatible, and environmentally sustainable lithium-ion batteries, contributing to the global transition toward resilient clean energy technologies.
Keywords: lithium-ion batteries; anode; low-temperature; green synthesis; type of access: embargo